2016
DOI: 10.1039/c5ra22537j
|View full text |Cite
|
Sign up to set email alerts
|

Charge-controlled switchable methane adsorption on heteroatom-doped BNNSs

Abstract: The adsorption behavior of methane (CH4) on neutral and charged states of Al-, C-, P- and Si-doped boron nitride nanosheets (BNNSs), is investigated using the density functional theory (DFT) method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Nanotubes have been extensively studied as potential adsorbents in sensing nanomaterials. Lin et al [26] made a comprehensive study on the effect of transition metal decoration on boron nitride nanotubes, whereas elements, such as aluminium, gallium and germanium have been widely used as a spread on nanotubes overall [27][28][29][30]. Other studies have shown that even the introduction of non-metal atoms, such as oxygen, can activate the overall surface of nanomaterials [31].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotubes have been extensively studied as potential adsorbents in sensing nanomaterials. Lin et al [26] made a comprehensive study on the effect of transition metal decoration on boron nitride nanotubes, whereas elements, such as aluminium, gallium and germanium have been widely used as a spread on nanotubes overall [27][28][29][30]. Other studies have shown that even the introduction of non-metal atoms, such as oxygen, can activate the overall surface of nanomaterials [31].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, compared to pure nanomaterials, it can be said that decorated nanomaterials have a higher efficiency [23]. Aluminum and gallium and germanium are the elements that have been widely used to activate the surface of nanosheets in theoretical studies [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, decorated nanomaterials exhibit different resistivity compared to their pure counterparts, a parameter that can be tuned to achieve high sensitivity when used in gas sensors [44]. Aluminum, gallium, and germanium are the elements that have been mostly investigated theoretically for activating the surface of nanotubes [45][46][47][48]. Lin et al [49] provide a comprehensive study on the effect of transition metal doping to sheets of BNNTs.…”
Section: Introductionmentioning
confidence: 99%